Annelated Pyridines as Highly Nucleophilic and Lewis Basic Catalysts for Acylation Reactions. Issue 20 (15th March 2013) - Tandon, Raman; Unzner, Teresa; Nigst, Tobias A.; De Rycke, Nicolas; Mayer, Peter; Wendt, Bernd; David, Olivier R. P.; Zipse, Hendrik
Abstract New heterocyclic derivatives of 9‐azajulolidine have been synthesized and characterized with respect to their nucleophilicity and Lewis basicity. The Lewis basicity of these bases as quantified through their theoretically calculated methyl‐cation affinities correlate well with the experimentally measured reaction rates for addition to benzhydryl cations. All newly synthesized pyridines show exceptional catalytic activities in benchmark acylation reactions, which correlate only poorly with Lewis basicity or nucleophilicity parameters. A combination of Lewis basicity with charge and geometric parameters in the framework of a three‐component quantitative structure–activity relationship (QSAR) model is, however, highly predictive.